Lead-free piezoelectric ceramic and preparation method thereof
By introducing CuO doping in lead-free piezoelectric ceramics, the orthogonal-tetragonal phase boundary is constructed, and the mutual constraints between high voltage electrical coefficient and high mechanical quality factor are solved, and the comprehensive optimization of high voltage electrical performance and low loss of ceramics is achieved.
Patent Information
- Application Number
- CN202411787137.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
AI Technical Summary
When existing lead-free piezoelectric ceramics pursue high voltage coefficient and high mechanical quality factor, the two parameters have mutual constraints and are difficult to achieve at the same time.
By introducing CuO for doping, the orthogonal-tetragonal phase boundary is constructed, the doping amount of CuO is controlled, defective dipoles are introduced, and multiphase coexistence and nanoscale domains are maintained, thereby improving piezoelectric performance and mechanical quality factor.
The high voltage electrical coefficient and high mechanical quality factor of lead-free piezoelectric ceramics are achieved, which significantly improves the overall performance of the ceramics.
Smart Images

Figure CN119528571A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of piezoelectric ceramics, and in particular to lead-free piezoelectric ceramics and a preparation method thereof. Background Art
[0002] Piezoelectric ceramics are a kind of mechanical-electric conversion material that is easy to industrialize and has excellent performance. They are widely used in aerospace, medical, military and daily life. Among them, lead zirconate titanate-based ((Pb,Zr)TiO3, PZT) ceramics have always dominated the market due to their excellent performance, but the Pb volatilization produced during the production process of PZT ceramics is very harmful to the human body and the environment. In order to limit the use of toxic elements such as Pb in electrical equipment, the European Union introduced the "Directive on the Restriction of the Use of Certain Hazardous Substances in Electrical and Electronic Equipment" Act (RoHS). In order to replace lead-based piezoelectric ceramics, a large number of researchers have begun to pay attention to lead-free piezoelectric ceramics. Potassium sodium niobate-based ((K,NaNbO3), KNN) ceramics have attracted much attention among lead-free piezoelectric ceramics due to their good piezoelectric properties and high Curie temperature.
[0003] In high-power devices with resonant frequencies ranging from a few kilohertz to several megahertz, there are also many applications of piezoelectric ceramics, such as ultrasonic cleaning, piezoelectric welding, etc. However, high-power devices are often limited by internal power consumption in their application scenarios. Internal losses, including elastic loss and piezoelectric loss, are usually dissipated in the form of heat energy, which also tests the thermal stability of the material. For the selection of piezoelectric ceramics for the preparation of high-power devices, on the one hand, it is hoped that the piezoelectric ceramics have a higher piezoelectric coefficient (d 33 ) to ensure its electromechanical properties, on the other hand, it is hoped that the piezoelectric ceramics have a high mechanical quality factor (Q m ) to reduce its energy loss. However, the two parameters are mutually restrictive. Ceramics with high piezoelectric coefficients often have ferroelectric domains that are easy to flip, while ceramics with high mechanical quality factors generally hope to pin the ferroelectric domains to make them difficult to flip. 33 High Q m KNN ceramics become a difficulty.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] To solve the problems in the background technology, the present invention provides a lead-free piezoelectric ceramic and a preparation method thereof, wherein the piezoelectric ceramic has both high piezoelectricity and high mechanical quality factor.
[0006] In order to achieve the above object, the first technical solution adopted by the present invention is; Lead-free piezoelectric ceramics have the general formula: 0.95(K 0.48 Na 0.52)NbO3-0.05(Bi 0.5 Na 0.5 )HfO3-0.002Fe2O3-xCuO, where 0.005≤x≤0.015.
[0007] Preferably, x=0.01.
[0008] The second technical solution adopted by the present invention is: A method for preparing lead-free piezoelectric ceramics, comprising: K2CO3, Na2CO3, Bi2O3, HfO2, Fe2O3, and Nb2O5 are mixed according to a stoichiometric ratio and then ball-milled for the first time to obtain a first slurry; The first slurry is dried and then pre-calcined to obtain a pre-calcined powder; Adding CuO to the pre-calcined powder, and performing a second ball milling to obtain a second slurry; After the second slurry is dried, an adhesive is added to perform mechanical forming and binder removal to obtain a sheet; The sheet is placed in an air-tight environment for sintering, cooling and polarization.
[0009] Preferably, the first ball milling uses anhydrous ethanol as the ball milling medium and the ball milling is performed at a rotation speed of 258 r / min for 12-14 h.
[0010] Preferably, the pre-sintering method is to increase the temperature from room temperature to 850-950°C at a heating rate of 3°C / min, keep the temperature at the highest temperature for 5-7h, and cool it down naturally.
[0011] Preferably, the sintering method is to heat to 1000°C at a heating rate of 5°C / min, then heat to 1070-1090°C at a heating rate of 3°C / min, and keep the temperature for 180-240 minutes.
[0012] Preferably, the DC electric field strength of the polarization is 2-3 kV / cm, and the polarization time is 20-30 min.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention introduces CuO for doping on the basis of constructing an orthorhombic-tetragonal phase boundary (OT phase boundary). By controlling its doping amount, not only defect dipoles can be introduced, but also multi-phase coexistence and nano-scale domains can be maintained. Multi-phase coexistence and nano-scale domains ensure a lower polarization barrier, thereby maintaining a high piezoelectric coefficient; defect dipoles can effectively inhibit domain wall motion and improve the mechanical quality factor; acceptor doping based on phase boundary construction significantly improves both the piezoelectric coefficient and the mechanical quality factor. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1This is a comparison chart of various properties of ceramics in experimental group 2 and control group 1; Figure 2 (a) is the frequency impedance diagram of the ceramics in the experimental group 2 and the control group 1, and (b) is the frequency phase angle diagram of the ceramics in the experimental group 2 and the control group 1; Figure 3 PFM test results of ceramics in experimental group 2, control group 1 and control group 2. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.It should be understood that these descriptions are exemplary only, and are not intended to limit the scope of the present invention.In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.Unspecified conditions in the embodiments are carried out according to the conditions of normal conditions or manufacturer recommendations.Reagents used or instruments that do not specify manufacturers are conventional products that can be purchased and obtained commercially.
[0016] The first embodiment of the present invention provides a lead-free piezoelectric ceramic, which has the general formula: 0.95(K 0.48 Na 0.52 )NbO3-0.05(Bi 0.5 Na 0.5 )HfO3-0.002Fe2O3-xCuO, where 0.005≤x≤0.015.
[0017] The high voltage coefficient (d 33 ) High mechanical quality factor (Q m ) lead-free piezoelectric ceramics are achieved by combining phase boundary construction with acceptor doping. First, the OT phase boundary is constructed at room temperature by doping multiple components, thereby greatly improving the piezoelectric performance. The present invention firstly 0.48 Na 0.52 )NbO3 is added with 0.05(Bi 0.5 Na 0.5 )HfO3-0.002Fe2O3 (hereinafter referred to as "BNH-Fe") can effectively improve the piezoelectric performance of KNN, but at the same time the mechanical quality factor will also be significantly reduced. Then, appropriate acceptor doping is performed, using low-valent ions Cu 2+ Substituting high-valent ion Nb 5+ Generate oxygen vacancies and combine with them to form defect dipoles and , pinning the ferroelectric domain while basically not changing the phase transition temperature, improving the mechanical quality factor and reducing the loss. In addition, the appropriate doping amount can not only introduce defect dipoles, but also maintain multi-phase coexistence and nanoscale domains, ensuring a lower polarization barrier, thereby maintaining a high d 33 Defect dipoles can effectively suppress domain wall motion, reduce losses, and improve Q m The combined effect of these two mechanisms ensures that 33 will not be significantly reduced, and Q m Significantly improved.
[0018] In a preferred embodiment, the optimal value of x is 0.01. When x=0.01, the performance of the lead-free piezoelectric ceramic is d33~340pC / N, Q m ~256.
[0019] A second embodiment of the present invention provides a method for preparing a lead-free piezoelectric ceramic, comprising: K2CO3, Na2CO3, Bi2O3, HfO2, Fe2O3, and Nb2O5 are mixed according to a stoichiometric ratio and then ball-milled for the first time to obtain a first slurry; The first slurry is dried and then pre-calcined to obtain a pre-calcined powder; Adding CuO to the pre-calcined powder, and performing a second ball milling to obtain a second slurry; After the second slurry is dried, an adhesive is added to perform mechanical forming and binder removal to obtain a sheet; The sheet is placed in an air-tight environment for sintering, cooling and polarization.
[0020] It should be noted that the key point of this embodiment is to add CuO after pre-firing. Ball milling method, pre-firing method, sintering method, polarization method, etc. are all commonly used KNN ceramic preparation methods in the field, and can be adaptively selected by technicians in this field according to the raw materials.
[0021] Exemplarily, the first ball milling uses anhydrous ethanol as the ball milling medium and is performed at a rotation speed of 258 r / min for 12-14 h.
[0022] Exemplarily, the pre-firing method is to increase the temperature from room temperature to 850-950° C. at a heating rate of 3° C. / min, keep the temperature at the highest temperature for 5-7 hours, and cool it down naturally.
[0023] Exemplarily, the sintering method is to heat to 1000° C. at a heating rate of 5° C. / min, then heat to 1070-1090° C. at a heating rate of 3° C. / min, and keep the temperature for 180-240 min.
[0024] Exemplarily, the DC electric field strength of the polarization is 2-3 kV / cm, and the polarization time is 20-30 min.
[0025] In order to make the present invention more clear, the lead-free piezoelectric ceramics and their performance are described in detail below through a number of specific embodiments.
[0026] Example 1 Lead-free piezoelectric ceramics, the general formula is: 0.95(K 0.48 Na 0.52 )NbO3-0.05(Bi 0.5 Na 0.5 )HfO3-0.002Fe2O3-xCuO. Set up multiple experimental groups and control groups, as follows: Experimental group 1: x=0.005; Experimental group 2: x=0.01; Experimental group 3: x=0.02; Control group 1: x=0; Control group 2: x=0.03.
[0027] The preparation method of lead-free piezoelectric ceramics is: (1) Ingredients and ball milling K2CO3 (analytical grade 99%), Na2CO3 (analytical grade 99.8%), Bi2O3 (analytical grade 99.999%), HfO2 (analytical grade 99%), Fe2O3 (analytical grade 99%) and Nb2O5 (analytical grade 99.5%) were used as raw materials, mixed according to the stoichiometric ratio, and after mixing, anhydrous ethanol was used as the ball milling medium, and the mixture was ball milled at a speed of 258 r / min on a planetary ball mill for 12-14 hours.
[0028] (2) Pre-sintering and secondary ball milling The fully mixed slurry was dried and transferred to a crucible. The temperature was raised from room temperature to 850-950°C at a heating rate of 3°C / min, and then kept at the highest temperature for 5-7 hours and cooled naturally. CuO was added to the pre-sintered powder according to the molar ratio of each experimental group and the control group, and then a secondary ball milling was performed for 12 hours to mix KNN-BNH-Fe and CuO (99%) evenly.
[0029] (3) Mechanical forming After the mixed slurry is dried, an appropriate amount of 5wt% polyvinyl alcohol aqueous solution (PVA) is added and mixed thoroughly. The dried powder is sieved, and then pressed into discs with a diameter of ~10mm and a thickness of ~1mm using a mold and a tablet press at a pressure of 300MPa. The pressed discs are placed in a muffle furnace and slowly heated to 850℃ for 17-19 hours, kept warm for 120 minutes, and then naturally cooled. The excess binder and moisture in the discs are finally removed by slowly heating and keeping warm for a long time, i.e., the debinding step.
[0030] (4) Sintering The debinded wafer is placed in an air-tight environment for sintering. The sintering procedure is to first heat to 1000°C at a heating rate of 5°C / min, then heat to 1070-1090°C at a heating rate of 3°C / min, keep at this temperature for 180-240 minutes, and then cool with the furnace.
[0031] (5) Polarization The surface of the sintered ceramic sheet is polished with a sand disc, and then silver paste is applied on both sides. It is placed in a muffle furnace and heated to 550-650℃ at 5℃ / min, then kept warm for 10-20min, and then cooled naturally. The ceramic sheet covered with silver electrodes is placed on a baking plate and heated for 10-20min, and then 2-3kV / cm DC is applied on both sides of the sheet under the protection of silicone oil for polarization, and the polarization time is 20-30min.
[0032] The performance of the lead-free piezoelectric ceramics prepared in the above experimental groups and the control group was tested, and the results are shown in Table 1.
[0033] Table 1 Performance of lead-free piezoelectric ceramics in the experimental and control groups .
[0034] As shown in Table 1, with the increase of Cu doping amount, d 33 The overall trend is downward, and it stabilizes at around 340pC / N when x=0.005-0.02; Q m As the doping amount increases, it first increases and then decreases, reaching a maximum value of 250 when x=0.01. Therefore, it can be considered that when x=0.01, the ceramic obtains the best comprehensive performance.
[0035] A multi-performance comparison was conducted between the experimental group 2 and the control group 1. The results are as follows Figure 1 As shown. Figure 1 It can be seen that the ceramic performance of control group 1 without Cu doping is d33~390pC / N, Q m ~60, the performance of the ceramics in experimental group 2 after doping with Cu is d 33 ~340pC / N, Q m ~256. Without excessively reducing the piezoelectric performance, the mechanical quality factor of the ceramic has been greatly improved. In addition, the coercive field is slightly reduced and the loss is greatly reduced.
[0036] The frequency impedance diagram (Impedance |Z|) and frequency phase angle diagram (Phaseangle) of experimental group 2 and control group 1 are as follows: Figure 2(a) and (b). It can be observed that the maximum phase angle of experimental group 2 is closer to 90°, indicating that the polarization effect is better. In addition, the impedance value corresponding to the resonant frequency of experimental group 2 is smaller, which also indicates that its loss is lower and the mechanical quality factor is larger.
[0037] The ceramics of experimental group 2, control group 1, and control group 2 were subjected to piezoelectric force microscopy test (PFM test) to observe the ferroelectric domains of the ceramic samples. The results are as follows: Figure 3 As shown. The first two columns are the piezoelectric response diagrams (Amplitude) of the ceramics, and the third column is the phase distribution diagram (Phase). It can be observed that the ceramics in the control group 1 have both large ferroelectric domains and fine nanodomains, which are similar to the ferroelectric domain morphology of the previous high-voltage KNN ceramics and present a mixed distribution. The ferroelectric domains of the ceramics in the experimental group 2 become fine and concentrated because the defect dipoles generated by CuO doping are distributed on the domain walls, hindering the formation of large domains. Theoretically, nanodomains are easy to flip, and the piezoelectricity should be higher, but the presence of defect dipoles hinders domain flipping. The ferroelectric domains of the ceramics in the control group 2 become broken islands because the doping amount is too high, and the excessive CuO directly destroys the formation of ferroelectric domains.
[0038] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. Lead-free piezoelectric ceramics, characterized in that Its general formula is: 0.95(K 0.48 Na 0.52 )NbO3-0.05(Bi 0.5 Na 0.5 )HfO3-0.002Fe2O3-xCuO, in which 0.005≤x≤0.
015.
2. The lead-free piezoelectric ceramic according to claim 1, characterized in that: x=0.01。 3. The method for preparing the lead-free piezoelectric ceramic according to claim 1 or 2, characterized in that: Include: K2CO3, Na2CO3, Bi2O3, HfO2, Fe2O3, and Nb2O5 are mixed according to a stoichiometric ratio and then ball-milled for the first time to obtain a first slurry; The first slurry is dried and then pre-calcined to obtain a pre-calcined powder; Adding CuO to the pre-calcined powder, and performing a second ball milling to obtain a second slurry; After the second slurry is dried, an adhesive is added to perform mechanical forming and binder removal to obtain a sheet; The sheet is placed in an air-tight environment for sintering, cooling and polarization.
4. The preparation method according to claim 3, characterized in that: The first ball milling used anhydrous ethanol as the ball milling medium and was carried out at a speed of 258 r / min for 12-14 h.
5. The preparation method according to claim 3, characterized in that: The pre-sintering method is to increase the temperature from room temperature to 850-950°C at a heating rate of 3°C / min, keep the temperature at the highest temperature for 5-7h, and cool it down naturally.
6. The preparation method according to claim 3, characterized in that: The sintering method is to heat to 1000°C at a heating rate of 5°C / min, then heat to 1070-1090°C at a heating rate of 3°C / min, and keep warm for 180-240 minutes.
7. The preparation method according to claim 3, characterized in that: The polarization DC electric field strength is 2-3 kV / cm, and the polarization time is 20-30 min.
Citation Information
Cited By
Ternary-system potassium-sodium niobate-based leadless piezoelectric ceramic and preparation method thereof
CN119912260A